A CFD model for the oil discharge ratio in rotary compressors. (March 2015) - Wu, Jianhua; Hu, Jiehao; Zhang, Jie; Sun, Min; Wang, Gang; Chen, Ang
The research on oil discharge ratio (ODR) of rotary compressors used for room air conditioners is very important to improve the performance and reliability of the compressors and their systems. This paper presents a detailed computational fluid dynamics (CFD) simulation model for the refrigerant gas flow and oil droplet flow within the shell of the compressor, which is used for investigating ODR of the compressor subjected to design changes or under different operating speeds. The geometry of the rotary compressor and its oil separating burden was presented. The CFD simulation is based on the discrete phase model (DPM). The oil droplet size distribution was defined by the Rosin–Rammler diameter distribution method. The boundary conditions of the refrigerant gas and oil droplets were established. Validation of the CFD model has been made by measuring ODR of a rotary compressor used in the high efficiency air room conditioner for different design configurations and an inverter rotary compressor with R410A. The simulation ODRs of the compressor agree within 11% of the experimental-measured ODRs. The ODR of compressor could be reduced effectively by some technique.